Avaliação da adesão microbiana em chapas de aço inoxidável AISI 304 soldadas pelo processo MIG/MAG convencional com foco na formação de biofilme na indústria de lacticínio - Batista, Marcio de Andrade (2017)
The objective of this work is to evaluate the microbial adhesion process that occurs on surfaces of AISI 304 austenitic steels used in the manufacture of tanks and heat exchangers in dairy products that benefit the milk in nature and / or cheese production. The very nature of the treated material (raw milk) favors the growth of biofilm-forming microorganisms. The adhesion process was verified in loco in exchangers and in receiving and cooling tanks of the product. To evaluate the formation of the biofilm and to correlate with the welding process, strands were deposited on 304 stainless steel sheet using the MIG / MAG process. After the welds, the test plates were immersed in receiving tanks of the raw milk, remaining exposed for 06 hours. The plates were subjected to CIP (clean in place) processes, in the same way as containment and receiving tanks. Microbiological evaluations were performed, as well as the collection of Swab in the zones of the ZAC (zone affected by heat) and root reinforcement, already predetermined in order to identify the microbiological adhesion. The concept of partition coefficient for the welded surface interface, biofilm and milk flow was established. The concept of ADPS (Preferential Adhesion in Welding) was created in order to establish a correlation between the position of microbial adhesion, with the respective formation of the biofilm versus the area of welding, as ZAC, root reinforcement or base material. From the obtained results the preferential adhesion area was identified and the variables responsible for such effect.